PENGARUH DISTRIBUSI PENDAPATAN TERHADAP KEMISKINAN DI INDONESIA - Rima Umami Hasibuan; Rizqi Sahdila (CV. ADIBA AISHA AMIRA, 2023)
This research was motivated by a lack of understanding and problems faced, especially in Indonesia, namely regarding the influence of income distribution on poverty. The aim of this research is to provide some understanding of the problems faced by the Indonesian nation in achieving the goals of prosperity and prosperity for all its people. Namely understanding the distribution of income in economic development regarding the welfare of society. Income distribution is related to poverty, in fact until now the problem of poverty has not been fully resolved. Lack of equal distribution of income and other problems, where poverty has complex problems whose root causes are like tangled threads that are interconnected with each other making it difficult to break the chain. The results of this research are that income distribution is still unequal, giving rise to the level of poverty in Indonesia